(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Exclusive Breast feeding is implies feeding of breast milk is enough for the baby up to six months of life and no other food is necessary during this time. Objective: The main objective of this study is to study the feeding practice of newborn babies in first week of life. Methods: This study was a cross-sectional study conducted on mothers who have done C-section. About 120 sample were interviewed in Dhaka Medical College Hospital and Pan Pacific Hospital Ltd, Dhaka. Pretested structured questionnaire was used for data collection. Results: The result showed that showed that one-third of the infants 84 (70%) were between the ages of 1 to 2 days and 29 (24.2%) were between the age of 3 to 4 days and the rest 7 (5.8%) were greater than 4 days and about half (53%) mothers initiate breast feeding within one hour after delivery. Besides study found that more than half of mothers 67(55.8%) were fed 5-8 time, 40 (33.4%) mother were fed 8-12 time and 13 (10.8%) mothers were fed per day 12-16 time and about 82% mothers use water as an extra feed of their child. Conclusion: The study result does not represent the country situation and should not generalize. Further study is needed for more specific information and generalization. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21028